Factors influencing clinical after effects of post orthognathic surgery - An observational clinical study - Saba Nasreen; Mohammed Saif Tagala; Sandeep Kumar Samal; Abhinav Raj Gupta; Ram Prasad Sah; Debarshi Bhattacharjee (Wolters Kluwer Medknow Publications, 2021)
Background: For maintaining the occlusion, screws to anchor bones are needed to be used in transalveolar manner to get the intermaxillary fixation in participants with no preoperative orthodontic treatment or participants with loose or broken appliances. Aims: The present clinical trial was hence aimed to assess the postoperative complications following orthognathic surgical repair of skeletal malocclusion. Materials and Methods: Forty-two participants were divided into two groups (n = 22). In Group I, predrill was done to create the holes in transalveolar position before screw insertion. For Group II, self-cutting screws were used without the drills. The radiographs were then taken to assess the associated root injuries. To evaluate the effect of different steroid doses on the pain, nerve healing, and swelling, the participants were divided into three groups (n = 14). Plate removal and associated factors were also evaluated. Collected data were statistically analyzed. Results: In Group where no predrill was done, no root injuries were seen. Considerably less facial edema was observed in Group II and III compared to control Group I. This difference was statistically significant with a P value of 0.2057. At 1 week, 3 months, and 6-month postoperatively in Group II and Group III, no significant difference was seen. No significant difference in the postoperative pain between the groups was seen (P = 0.85103). Neurosensory Visual Analog Score measurement revealed no significant difference between three groups at 6 months with the P value of 0.81821. Conclusion: The present study concludes that risk for the root injury is possessed by the screws that require predrill, whereas the self-drilling screws had no risk for root injury.